How do teachers of literacy learn what they need to know? - Villanueva, Victor A. (2004)
Thirty preschool and elementary school teachers attended and complete a ten-day inservice professional development seminar on literacy learning, difficulties and intervention. The teachers were asked to take a 15-item subject matter knowledge test before and after the seminar. The test items covered concepts in literacy learning that research have deemed important for literacy teachers to know. The results suggest a gap in what teachers know and what they should know. Results also show that professional development programs can effectively address this gap in conceptual knowledge. In addition, the study also provided information on which concepts are more readily learnt in comparison to others. Finally this study revealed a possibility that a teacher's length of teaching experience has an effect on subject matter knowledge development. From these, recommendations for teacher development are drawn.
Keywords: Elementary school teachers -- In-service training; Preschool teachers -- In-service training; Literacy education -- Research